2021
DOI: 10.1080/07853890.2021.1991591
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immune-inflammation index is a promising non-invasive biomarker for predicting the survival of urinary system cancers: a systematic review and meta-analysis

Abstract: Objective: Systemic immune-inflammation index (SII) has been reported in numerous studies to effectively predict the survival outcomes of urinary system cancers; however no agreement has been reached. This meta-analysis aimed to explore the prognostic significance of pre-treatment SII in tumours of the urinary system. Methods: Relevant published articles were selected from Web of Science, PubMed, Embase, and the Cochrane Library up to 30 August 2020. The hazard ratios (HRs) with 95% confidence intervals (CIs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 46 publications
0
32
0
1
Order By: Relevance
“…A higher SII corresponds to higher platelet/neutrophil and/or lower lymphocyte counts. Thus, an elevated SII indirectly symbolizes the deficiency of immune function and the enhancement of tumor aggressiveness in cancer patients ( 32 ). As a composite immune index, SII may have better predictive power than parameters such as NLR, PLR, and LMR.…”
Section: Discussionmentioning
confidence: 99%
“…A higher SII corresponds to higher platelet/neutrophil and/or lower lymphocyte counts. Thus, an elevated SII indirectly symbolizes the deficiency of immune function and the enhancement of tumor aggressiveness in cancer patients ( 32 ). As a composite immune index, SII may have better predictive power than parameters such as NLR, PLR, and LMR.…”
Section: Discussionmentioning
confidence: 99%
“…First, Zhang et al [ 33 ] suggested that a high SII was related to poor prognosis in breast cancer patients and clinicopathological features that indicated tumor progression. Additionally, Li et al [ 34 ] reported that SII could serve as a promising noninvasive biomarker to assess the prognosis of patients with urinary system cancer. Another meta-analysis showed that a higher pre-treatment SII was significantly associated with poorer survival outcomes and several clinical characteristics in GC [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been also suggested that as the SII includes three different cells, it may better reflect the inflammatory status than other indices, which are typically based on two cells such as NLR and PLR or the lymphocyte-to-monocyte ratio. The first study on SII reported that it strongly predicted poor prognosis in several types of gastrointestinal and other systems malignancies [ 42 ]. Following these studies, the association between the SII and cardiovascular diseases has been increasingly investigated.…”
Section: Discussionmentioning
confidence: 99%